say fast i need this answer
Attachments:
![](https://hi-static.z-dn.net/files/dde/2b9d51ad7e4c8e783405962db427755a.jpg)
Answers
Answered by
1
Let
=>5/(x-1)+1/(y-2)=2 ...(i)
And ,6/(x-1)-3/(y-2)=1 ...(ii)
Multiplying eq. By 3 we get
=>15/(x-1)+3/(y-2)=6 ..(iii)
Now, adding eq. (ii) and (iii) we get,
=>21/(x-1)=7 x=3+1=4
Now, putting x=4 in eq (ii)
We get,
=>y=3+2=5
Hence,x=4 and y=5
Hope it helps
=>5/(x-1)+1/(y-2)=2 ...(i)
And ,6/(x-1)-3/(y-2)=1 ...(ii)
Multiplying eq. By 3 we get
=>15/(x-1)+3/(y-2)=6 ..(iii)
Now, adding eq. (ii) and (iii) we get,
=>21/(x-1)=7 x=3+1=4
Now, putting x=4 in eq (ii)
We get,
=>y=3+2=5
Hence,x=4 and y=5
Hope it helps
dolly81:
thanks for saying but i didn't find this opsition in our book
Similar questions